Fertilitas Spermatozoa Babi Landrace dalam Pengencer Modifikasi Zorlesco dengan Susu Kacang Kedelai - J A Tamoes; W M Nalley; T M Hine (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
A research has been done to study the effectiveness of Zorlesco extender and modified Zorlesco extender with soymilk to maintain sperm fertility of landrace boar preserved at 18˚C. Semen was collected twice a week by hand massage from 2 heads of ± 2.5 years old landrace boar. A Completely Randomized Design with 4 treatments and 5 replications was used to organized the experiment. The fresh evaluated semen were extended with zorlesco P(0), zorlesco + hand made soymilk P(1), zorlesco + MetabolisTM soymilk P(2), and zorlesco + MelileaTM soymilk P(3). Extended semen were preserved at 180C. Analysis of variance and Duncan test were used to analyzed data of motility and viability of sperm. The result showed that the modification of diluent Zorlesco added with 5% soymilk could not defend by sperm motility and viability spermatozoa compared with Zorlesco for 42 hours storage (P<0.05).Keyword: Soymilk, modified zorlesco, sperm motility, sperm viability, landrace boar